Distributed Ledger Technologies, Value Accounting, and the Self Sovereign Identity - Manski, Sarah (Frontiers in Blockchain, 2020)
Organizations are utilizing new technologies including distributed ledgers to challenge value accounting within global capitalism. This paper investigates new radical digital accounting practices underpinning this form of organizing and explores the development of new technologies of value accounting practices enabled by distributed ledger technologies, such as generative value accounting. This theory paper makes use of the concept of the sociotechnical imaginary as it offers a framework for understanding how a technologist’s vision of the ideal future influences their design choices in the present with Holochain as a specific case.